Hematometra ec agenesis serviks, suspek MRKH - Anriani, Selvy; Candra Triastuti, Prastika; Bayu Dalem Putra, Gde Ngurah (Science Midwifery, 2023)
Background: Primary amenorrhea is the absence of menarche. After gon-adal dysgenesis, the Mayer-Rokitansky-Küster-Hauser (MRKH) syn-drome is the second most common cause of primary amenorrhea. Herein, we de-scribe how to diagnose and the treatment of MRKH. Case presentation: A 21-year-old lady with complaints of abdominal pain in the lower portion of the navel for the past 4 months that has worsened in the previous week, accompanied by complaints of urinat-ing slowly and feeling agony. The patient claimed to be single, to have never had coitus, and to have never menstruated previously. Physical examination revealed tanned 5 breasts, axillary hair (+), and an ab-dominal lump palpable on the 2nd finger region below the navel with pain. There were 5 tanner pubic hairs, labia major +/+, labia minor +/+, and a hymen bulging (-) in the vagi-nal area. A cystic mass pressing on the anterior region of the rectum, hy-men (+) impression of the vaginal septum, and vaginal introitus (-) are all felt when examined in the anus. Uterine dimensions 10x5x4 cm, hypoechoic mass in the uterine cavity, free fluid (-), cervical canal not evident, vaginal introitus (-), hematocol-pos (-), and abdominal ultrasonography results re-vealed no abnormali-ties. Other tests were not carried out. A laparotomy was conducted to remove the hematometra based on the results of clinical and support-ive investigations. Conclusion: This is a rare occurrence of cervical agenesis, occurring in 1 in 80,000 women. Additional tests are required in this case to con-firm the diagnosis of MRKH. The treatment in this scenario seeks to reduce pain and evacuate blood, so that subsequent treatment to re-store the cervical canal at a more comprehensive health service cen-ter is required.